RISING AMBIENT AIR POLLUTION AND RISK OF RESPIRATORY IMPAIRMENT IN TRAFFIC POLICEMEN - RITA SINGH; RAJIV GARG; MASTAN SINGH; JITENDRA K CHAUDHARY (International Journal of Pharma and Bio Sciences, 2014)
The particles emitted from vehicular exhaust usually include particles less than 10 micron diameter (PM10) which get accumulated in the lungs and produce respiratory impairments. This study was taken up to assess the effect of vehicular exhaust on their pulmonary functions readings. The spirometric analysis of traffic policemen revealed FEV1 2.35 L, FVC 3.19L and PEF 7.8 L/s when compared with those with controls in whom the values of FEV1, FVC and PEF were 4.20 L, 4.45 L and 8.47 L/s, respectively. The odd ratio for breathlessness, cough with expectoration, chest pain and irritation of therespiratory tract were 6.6, 3.7, 3.0 and 2.8 respectively. In the present study, we find rise of ambient air pollution as a result of vehicular pollution which may result in respiratory impairment of traffic policemen. It may be due to prolonged exposure of vehicular pollution, which causes a reduction in the lung function efficiency.